How Do Pacific Island Households and Communities Cope with Seasonally Absent Members? - Rohorua, Halahingano; Gibson, John; McKenzie, David; Garcia Martinez, Pilar (2012)
Households and communities in the Pacific islands are increasingly likely to have some of their most productive members regularly absent due to growing opportunities for seasonal work abroad. If these absences are costly for the family left behind, the net development benefits of seasonal migration will be less than what they appear from remittances and repatriated foreign earnings, and there might be a role for government policies in host and source countries to mitigate some of the effects of absence. This article provides the first evidence of how Pacific island households and communities are affected by and cope with seasonal absences. We find that Tongan households have succeeded in mitigating many of the potential adverse effects associated with seasonal separation of members, whereas households from Vanuatu with members participating in the RSE appear to have suffered some short-term costs in terms of diet and health.